Teologins queera dilemman - Ida Simonsson (Svensk Teologisk Kvartalskrift, 2013)
This article investigates a tension within queer theology, or more specifically between queer theory and Christian theology. Whereas queer theory seeks to deconstruct culturally constructed identities to trace the exclusions that are made in the name of cultural comprehensibility, theology explores the Christian identity as a means to strengthen it. The investigation focuses on the apparent conflict between the logic of a God-given Christian identity that dissolves all other identities, exemplified by Elisabeth Stuart's "Sacramental Flesh", and the theory of gender melancholia and this melancholia as constitutive for the gendered subject as presented by Judith Butler in Gender Trouble. However, this tension seems to be solved when focus is put on the possibility to see the Christian identity not as beyond cultural negotiation, but rather as in need to be enacted in culture. This is understood from two perspectives. First in terms of Butler’s theories of performativity – cultural constructs become corporeal through constant reenactments. Second, in terms of Serene Jones' understanding of the righteousness of faith as a righteousness that is given to the Christian to perform. Finally, the article argues that with this notion of the Christian identity as beyond human grasp, given from an eschatological horizon, but still always performed in culture and therefore always in need of revision, it is possible to hold together queer theory and Christian theology.